Hymenopteran Parasitoids of Leucotaraxis argenticollis (Diptera: Chamaemyiidae) and Leucotaraxis piniperda: Implications for Biological Control of Hemlock Woolly Adelgid (Hemiptera: Adelgidae). Issue 5 (11th August 2022) - Celis, Sabrina L; Dietschler, Nicholas J; Bittner, Tonya D; Havill, Nathan P; Gates, Michael W; Buffington, Matthew L; Whitmore, Mark C
Abstract: The hemlock woolly adelgid ( Adelges tsugae (Annand)) is a serious invasive pest of hemlock trees in eastern North America. Multiple biological control agents have been the focus of research aimed at pest management and conserving hemlock communities. Three promising A. tsugae specialist predators are the beetle Laricobius nigrinus (Fender) (Coleoptera: Derodontidae) and flies in the genus Leucotaraxis (Diptera: Chamaemyiidae), Leucotaraxis argenticollis (Zetterstedt), and Leucotaraxis piniperda (Malloch). However, these flies are vulnerable to parasitism by wasps in the genera Pachyneuron (Walker) (Hymenoptera: Pteromalidae) and Melanips (Walker) (Hymenoptera: Figitidae). This study explores parasitoid wasp interactions with these Leucotaraxis species in their native western North American range and potential impacts on the biological control program in the East. Leucotaraxis, La. nigrinus, and parasitoid emergences were observed from adelgid-infested foliage collected from Washington State and British Columbia in 2018, 2019, and 2020. Undescribed species of Pachyneuron and Melanips emerged from puparia as solitary parasitoids. Parasitoid emergence was positively correlated with Leucotaraxis emergence. Percent parasitism increased between February and July, with the months of June and July experiencing higher parasitoid emergence than Leucotaraxis . Differences in emergence patterns suggest that Pachyneuron may be more closely associated with Le. argenticollis as a host, and that Melanips may be associated with Le. piniperda . High parasitism in Leucotaraxis had no effect on La. nigrinus larval abundance, whereas the combined emergence of parasitoids and Leucotaraxis was positively correlated with La. nigrinus . This suggests that there is limited competition among these predators.